Developing Voice in Digital Storytelling Through Creativity, Narrative and Multimodality - Monica Nilsson (Seminar.net, 2010)
For Simon, who is nine years old, reading and writing are obstacles rather than tools. However, when offered the opportunity to create digital stories, Simon becomes deeply engaged. He creates complex stories within different genres based on a variety of subjects. He both expresses and creates meaning through his digital storytelling. He develops what Elbow calls ´voice.´ In the paper I argue that digital storytelling became a resource for Simon which triggered his interest in literacy because of two specific features: multimodality and narrative. Vygotsky’s work on development of  literacy and creativity comprise a theoretical point of departure and I claim that new media has the potential to play a significant role in this realm.